Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1080/09544828.2019.1676883
|View full text |Cite
|
Sign up to set email alerts
|

Social- and self-perception of designers’ professional identity

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 80 publications
(83 reference statements)
0
18
0
Order By: Relevance
“…For example, Gonzalez, Smith, and Youmans (2017) conducted a survey to compare what skills human factors students were learning in the classroom and what skills human factors professionals were actually using. Future research could also explore the professional identity of information science, by trying to specify more the two aspects, personal attributes and skills (Kunrath, Cash, & Kleinsmann, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Gonzalez, Smith, and Youmans (2017) conducted a survey to compare what skills human factors students were learning in the classroom and what skills human factors professionals were actually using. Future research could also explore the professional identity of information science, by trying to specify more the two aspects, personal attributes and skills (Kunrath, Cash, & Kleinsmann, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…At the personal level, creative entrepreneurs share two perceptions in society, namely self-perception and social perception. The individual's cognition of external norms depends on the self-perception of his/her behavioral characteristics or state (Kunrath et al, 2020 ). When self-concept is emphasized, creative entrepreneur's creativity is more susceptible to personal goals and needs.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, professors play a pivotal role in the initial development of their students' PI and ways of thinking, based on their teaching of the norms they believe a student should adhere to, reinforced via academic assessments (Murphy et al, 2015). Kunrath et al (2020) highlighted interviews where professors concluded that their focus when teaching was not just to provide the basic technical knowledge but to create a questioning and creative thinking mindset. As a result, students tend to align their perceptions with those of their professors (Trede, 2012) and their active learning choices during education.…”
Section: Literature Reviewmentioning
confidence: 99%